Automated and customizable quantitative image analysis of whole Caenorhabditis elegans germlines. - Toraason, Erik; Adler, Victoria L.; Kurhanewicz, Nicole A.; DiNardo, Acadia; Saunders, Adam M.; Cahoon, Cori K.; Libuda, Diana E. (Genetics, 2021)
Arranged in a spatial-temporal gradient for germ cell development, the adult germline of Caenorhabditis elegans is an excellent system for understanding the generation, differentiation, function, and maintenance of germ cells. Imaging whole C. elegans germlines along the distal-proximal axis enables powerful cytological analyses of germ cell nuclei as they progress from the pre-meiotic tip through all the stages of meiotic prophase I. To enable high-content image analysis of whole C. elegans gonads, we developed a custom algorithm and pipelines to function with image processing software that enables: (1) quantification of cytological features at single nucleus resolution from immunofluorescence images; and (2) assessment of these individual nuclei based on their position within the germline. We show the capability of our quantitative image analysis approach by analyzing multiple cytological features of meiotic nuclei in whole C. elegans germlines. First, we quantify double-strand DNA breaks (DSBs) per nucleus by analyzing DNA-associated foci of the recombinase RAD-51 at single-nucleus resolution in the context of whole germline progression. Second, we quantify the DSBs that are licensed for crossover repair by analyzing foci of MSH-5 and COSA-1 when they associate with the synaptonemal complex during meiotic prophase progression. Finally, we quantify P-granule composition across the whole germline by analyzing the colocalization of PGL-1 and ZNFX-1 foci. Our image analysis pipeline is an adaptable and useful method for researchers spanning multiple fields using the C. elegans germline as a model system.